2020
DOI: 10.17358/jabm.6.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Perilaku Penggunaan Internet Banking Sebagai Alat Transaksi Finansial

Abstract: Internet banking is one of the bank services to do financial and non-financial transactions via an internet network. Internet banking provides consumers' benefits such as fast, safe, convenient, and inexpensive transactions. Moreover, the bank gains business expansion and customer loyalty as their own benefits. Internet banking usage is influenced by perceived usefulness, perceived ease of use, visibility, enjoyment, social influences, attitude toward using, behavioral intention, and actual usage. The study's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
4
7
0
1
Order By: Relevance
“…Procedures for using Mendeley that are easy to understand will help complete work faster and student performance will be better. The result of this test is in accordance with research [9]; [7]; [13]; [8]; and [32] stating that perceived ease of use has a positive effect on perceived usefulness. From table 6, it can be concluded that perceived ease of use indirectly has a positive and significant effect on behavioral intention of use through perceived usefulness.…”
Section: Perceived Ease Of Use Has a Positive And Significant Effect ...supporting
confidence: 87%
See 2 more Smart Citations
“…Procedures for using Mendeley that are easy to understand will help complete work faster and student performance will be better. The result of this test is in accordance with research [9]; [7]; [13]; [8]; and [32] stating that perceived ease of use has a positive effect on perceived usefulness. From table 6, it can be concluded that perceived ease of use indirectly has a positive and significant effect on behavioral intention of use through perceived usefulness.…”
Section: Perceived Ease Of Use Has a Positive And Significant Effect ...supporting
confidence: 87%
“…The results of the same study conducted by Sana et al that the more user attitudes to use technology are formed, the more convinced these users will continue to use technology [27]. The results of these studies are in accordance with research [13]; [6]; [7]; and [27] where the results of the research on behavioral intention of use variables are directly influenced by the attitude towards using variables positively and significantly.…”
Section: Attitude Towards Using Has a Positive And Significant Effect...supporting
confidence: 77%
See 1 more Smart Citation
“…If an application is found difficult to utilize, then the application will no longer be used by customers. Generally, a system that is easier to use eventually becomes more useful for its users (Anjelina, 2018;Heryani, Simanjuntak & Maulana, 2020). Other than that, security covers the concept of administering personal data of fintech users, which includes maintaining confidentiality and providing confidence in security guarantees (Abdullatif, Purnaningsih & Simanjuntak, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Andre et al (2021) and Prastiawan et al, (2021) have all conducted research on the impact of perceived ease of use on behavioral intention to use technology. They found that perceived ease of use positively influences behavioral intention to use, while Heryani et al (2020) and Saidani et al (2022) found that it does not significantly affect behavioral intention to use digital payment applications in Jakarta. These findings suggest the need for further study on how perceived ease of use influences behavioral intention.…”
mentioning
confidence: 99%